Moderasi Beragama di Era Disrupsi Digital - Suheri, Suheri; Nurrahmawati, Yeni Tri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This study is to describe and utilize social media platforms as a strategy and media for preaching in conveying the values ​​of religious moderation in the era of digital disruption. The objects studied are the largest social media platforms used in Indonesia including Youtube, Whatsapp, Facebook, Instagram and so on. The type of research used is field research with a qualitative approach. The data collection technique used is qualitative by observing various videos, narrations, voices, flayers or images on various social media platforms. Then the data was analyzed using the interactive model analysis of Miles and Huberman. The results of this study indicate that conveying religious moderation to the millennial generation of digital disruption requires transformation and a da'wah approach that is in harmony with their world, namely the transformation of the value of religious moderation from oral to online, the transformation of traditional da'wah into digital technology, the transformation from the delivery of the real world to the virtual world, transformation from local to global, the transformation from conventional is slow, takes space and time and even tends to take a long time towards fast and instant da'wah.